De novo variants in KLF7 are a potential novel cause of developmental delay/intellectual disability, neuromuscular and psychiatric symptoms. Issue 5 (25th January 2018) - Powis, Z.; Petrik, I.; Cohen, J.S.; Escolar, D.; Burton, J.; van Ravenswaaij‐Arts, C.M.A.; Sival, D.A.; Stegmann, A.P.A.; Kleefstra, T.; Pfundt, R.; Chikarmane, R.; Begtrup, A.; et al.
Abstract : Due to small numbers of reported patients with pathogenic variants in single genes, the phenotypic spectrum associated with genes causing neurodevelopmental disorders such as intellectual disability (ID) and autism spectrum disorder is expanding. Among these genes is KLF7 (Krüppel‐like factor 7), which is located at 2q33.3 and has been implicated in several developmental processes. KLF7 has been proposed to be a candidate gene for the phenotype of autism features seen in patients with a 2q33.3q34 deletion. Herein, we report 4 unrelated individuals with de novo KLF7 missense variants who share similar clinical features of developmental delay/ID, hypotonia, feeding/swallowing issues, psychiatric features and neuromuscular symptoms, and add to the knowledge about the phenotypic spectrum associated with KLF7 haploinsufficiency. Abstract : A, Case series of 4 individuals with Krüppel‐like factor 7 ( KLF7 ) variants, structural interpretation of the variants and review of patients in the literature regarding the 2q33.3q34 deletion encompassing KLF7 and pathogenic mechanisms of KLF7 variants. B, Variants in KLF7 cause neurodevelopmental features such as developmental delay/intellectual disability, hypotonia, feeding/swallowing issues, psychiatric features and neuromuscular symptoms along with dysmorphic features, seizures and microcephaly.